Cost-benefit analysis of solar energy integration in buildings: a case study of affordable housing in Brazil - De Arruda, Roberto Nonato; Figueiredo, Karoline; Vasco, Diego A.; Haddad, Assed; Najjar, Mohammad K. (Frontiers in Built Environment, 2023)
The construction sector significantly impacts natural resource consumption, highlighting the need for increased global awareness of energy efficiency in buildings. Hence, the surge in demand for solar energy as a renewable energy source has been remarkable. This study aims to conduct a comprehensive cost-benefit analysis of solar energy utilization in residential buildings. A novel approach is presented, comparing photovoltaic panels and Solar Heating Systems (SHS) based on environmental and financial aspects. A case study of a Brazilian social interest residence is evaluated, simulating three models: Model 1 incorporates a grid-connected photovoltaic project with zero energy balance; Model 2 includes a grid-connected photovoltaic project with two solar panels with 340W each; and Model 3 integrates an SHS. The findings indicate that all proposed models are both technically and economically feasible. More specifically, Model 1 demonstrates superior performance in estimated energy generation, energy savings, and annual reduction of CO 2 emissions, while Model 3 excels in financial analysis. This research empowers decision-making processes for using photovoltaic panels and SHS, fostering energy efficiency and sustainability in buildings.